Genetics of migration timing in bar-tailed godwits : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Zoology at Massey University, Manawatū, New Zealand - Parody Merino, Ángela Mariá (Massey University, 2018)
Bird migration is one of the most amazing behaviours observed in nature and it fascinates because of its diversity and its – still – unclear reasons and origin. My thesis converges primarily two big areas of research in biology: ecology and genetics / genomics. The ecology part is the bird system (the godwit), which has been extensively studied and whose individual departure date has been proven to be exceptionally consistent. Studies of this kind are not possible without a suitable system, and longitudinal behavioural records of the same individuals are not easy to obtain. The genetics and genomics are, without doubt, the biggest part of this thesis. What can we learn about how DNA encodes biological rhythms in natural populations taking godwits as an example? There is a huge amount of literature on chronobiology, mainly based on experiments with model organisms or caged individuals. Thanks to these experiments the elements (i.e. proteins and genes) involved in the biological clock have been identified and the characteristics of circadian and circannual rhythms have been described. However, it remains unclear how these elements link to an individual’s timing behaviour in nature. Extensive research on the migration timing of bar-tailed godwits (Limosa lapponica baueri) in New Zealand gave rise to an intriguing observation: individual’s departure dates seemed to be primarily driven by an ‘internal signal’, and this ‘internal signal’ was quite consistent across the years, while the population showed a departure-span of approximately a month. This raised questions such as: Are there elements of the internal clock that determines such within species (population) diversity and such intra-individual consistency? In my thesis research I first I assessed the population genetic structure of godwits related to migration time, a step that is necessary when trying to link phenotypes with genotypes. Then I used genomic approaches and integrated behavioural data to understand whether elements related to the ‘internal clock’ are associated to individuals’ migratory departure time in godwits. I found evidence of slight population genetic structure between northern and southern breeders as well as between earlier and later migrants departing from the stop-over in Asia, but not between earlier and later migrants from New Zealand. Detailed analyses of migration timing in relation to polymorphisms in clock (a gene implicated in other studies as potentially influencing migration timing) found no support for clock having any role in godwit migration timing. Analysis of variation in 120 genes associated with the internal clock, photoreception, the physiology the Hypothalamic-Pituitary-Gonadal Axis – which modulates the internal clock –, and fat metabolism and storage indicates that individual migration timing of godwits has a genetic basis to some degree, but differences between individuals seem to be associated with large numbers of genes of small effect rather than a few genes of large influence. Godwit migration timing therefore appears to be a complex trait in which genetic differences between individuals explain some of the variation timing, but a large amount of the variation observed is not explained by the suite of genes studied. It is possible that key genes exist that were not studied, and/or that non-genetic factors may be influencing an individual’s decision to migrate on a given day above and beyond the genetic influence. In general, this thesis contributes to the understanding of the nature of behaviours (i.e. genes-behaviour link) in natural populations, specifically in the area of chronobiology.
Keywords: Bar-tailed godwit -- Migration -- New Zealand; Bar-tailed godwit -- Genetics; Bar-tailed godwit -- Behavior; Migratory birds -- Behavior -- Genetic aspects; Chronobiology; Kūaka